Investigation of acoustic properties of snow-covered sea ice - R. A. Balakin; G. I. Vilkov (Лëд и снег, 2018)
The paper presents results of field observations of hydroacoustic characteristics of snow-covered ice cover in shallow seas of the Arctic shelf. The purpose of the research was to determine the quantitative characteristics of the reflection and absorption coefficients of sound from the bottom of the drifting ice cover, as well as the Doppler broadening of the frequency spectrum of acoustic signals depending on the thickness of the ice, the structure of the reflecting surface, the thickness of the snow cover, and the ice drift speed. The objective of the research was to obtain the data necessary for choosing optimal parameters of specialized hydroacoustic equipment designed to monitor ice conditions in the areas of operation of offshore oil and gas platforms. Researches were conducted in areas of active construction of engineering marine constructions and carrying out the transport operations. The research methodology was based on the use of an autonomous measuring complex, which for a long period was installed on the bottom of the sea at depths of 50 to 130 m. The recording system consisted of the following components: upward looking pulse sonar of the IPS-5 type produced by the Canadian company ASL; the Doppler meter of the ice drift speed ADCP (the RDI firm); and a RSM-7 electromechanical current meter. All devices operated in continuous mode with a measurement cycle of 1s, the results were recorded in memory and processed after lifting the devices to the surface. The time delays of signals reflected from the ice cover, as well as the amplitudes and variations of the sound attenuation depending on the reflectance and absorption coefficients were recorded in the memory of the up-looking sonar. Variations of time delays were used to calculate a settlement of ice formations and to determine the shape of the reflective surface, including the angles of inclination of ice keels. Doppler shift of frequency of reflected acoustic signals and broadening of the frequency spectrum were calculated using values of the ice drift speed and changes of immersion depths of hummocks. Acoustic characteristics were measured repeatedly during several seasons of each year from 2010 to 2017. This investigation made possible to obtain statistical estimates of the distributions of the reflection coefficient of the sound and the quantitative values of broadening of the frequency spectrum of acoustic signals depending on the angle of incidence of the acoustic rays, the nature of the irregularities and the structure of the reflective surfaces of ice and snow cover thickness and the drift speed. The results obtained by this research allowed reasonable choosing and calculating the basic characteristics of the hydroacoustic equipment intended for runtime diagnostics of ice cover in zones of marine engineering structures.